Estudo termodinâmico, cinético e de otimização da extração de óleo do farelo de arroz utilizando solventes renováveis - Ribas, Felipe Brondani Teixeira (2023)
The application of renewable solvents in the extraction of rice bran oil as a substitute for hexane is the focus of this dissertation. In the first case study, ethanol and ethyl acetate solvents were applied. To evaluate the interaction of these solvents with the oil, the UNIFAC model was chosen to determine the infinite dilution activity coefficient. Soxhlet extraction was used to determine the maximum possible yield. The fitting of experimental data to kinetic and thermodynamic models of mass transfer was conducted using the response surface methodology. The experimental data aligned with the kinetic model based on solid-liquid mass transfer. The thermodynamic study revealed that both solvents undergo endothermic, spontaneous and irreversible processes. Ethyl acetate exhibited higher extraction yields at the beginning and reached its highest yield in a shorter time interval due to better compatibility with oily compounds present in rice bran and its lower viscosity. For the second case study, the impact of temperature, solvent/solid ratio and water content on oil extraction yield using 2-MeTHF was evaluated. The JCOSMO software successfully demonstrates the charge density of solvent and solute molecules. Rice bran oil exhibited a higher FFA content compared to the first study. FTIR analysis identified functional groups in biomass and oils. XRD demonstrated the amorphous character of rice bran. Analysis of the response surface methodology revealed that temperature had the most significant influence on the extraction efficiency of both extractions. Increasing water content improved yield at lower solvent/solid ratios. The hydrated solvent outperformed the anhydrous solvent in extracting oil from rice bran. 2-MeTHF resulted in higher yields compared to hexane. Statistical analysis confirmed the good fit of the experimental data to the theoretical model. This study emphasizes the key parameters for achieving oil extraction efficiency, highlighting the superiority of 2-MeTHF over hexane. Both case studies demonstrated the possibility for optimizing rice bran extraction benefiting industries dependent on oil.